Alkali reaction inhibiting sandstone material and preparation method thereof

CN122940398APending Publication Date: 2026-10-20ZHONGTIANHANG (GUANGDONG) MATERIALS TRADING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337734.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

沙石骨料中含有的凝灰岩、燧石等活性二氧化硅组分,遇水泥孔溶液碱离子并在水分持续补给下,会生成吸水膨胀型碱硅凝胶,造成混凝土内部微裂、表层剥落,长期使用存在安全隐患

Benefits of technology

[0025]本发明的抑碱反应沙石新材料采用了由内至外的仿生矿化界面粘附层、介孔靶向抑碱层和硅烷交联疏水外层的三重复合涂层设计。通过多重协同作用,有效封闭了内部活性二氧化硅,从根源上抑制了碱-硅酸反应的发生,提升材料的抑碱效果。通过富含邻苯二酚基团的植物多酚与低钙硅比C-S-H凝胶复合构成有机-无机杂化网络,并配合水性高分子网络与氨基硅烷形成层间桥接结构,解决了传统介孔粉体或物理涂层在混凝土强力拌合条件下大量剥落、功能严重退化的工程痛点。材料外层采用氨基硅烷与烷基三乙氧基硅烷共水解缩聚形成的憎水交联网络,使改性沙石的水接触角达到了128°至142°,成功构建了高疏水抑碱防线,能够有效阻隔外界水分侵入,减少碱骨料反应所必需的水分传输通道,进一步提升抑碱长效性。介孔靶向抑碱层内负载可溶性锂盐的MCM-41介孔二氧化硅能够在骨料表面活性硅界面处定点释放锂离子,实现局部抑碱,而配伍的纳米偏高岭土则能引发微区地质聚合反应,有效防止了传统物理吸附容易导致的碱离子后期反吐失效问题,消除了长期服役中的安全隐患。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of building aggregate modification and concrete durability materials, and discloses a novel alkali-inhibiting sand and gravel material and its preparation method. The novel alkali-inhibiting sand and gravel material includes a sand and gravel matrix containing active silica and a triple composite coating covering the surface of the sand and gravel matrix. The preparation method is as follows: the alkali-active sand and gravel matrix is ​​sieved, washed with water to remove surface mud and powder impurities, dried, and cooled for later use; an aqueous solution containing plant polyphenols and calcium nitrate is prepared; the pretreated sand and gravel matrix is ​​dried for later use; lithium-loaded MCM-41 micro powder is prepared; the lithium-loaded MCM-41 micro powder and nano-kaolin are dispersed in a mixed solvent to form a stable suspension slurry; the sand and gravel are immersed in the slurry for impregnation and coated, and then dried and cured; aminosilane and alkyltriethoxysilane are mixed to obtain a silane composite modification liquid; the modification liquid is uniformly atomized and sprayed onto the surface of the sand and gravel, and cured at a constant temperature. After interlayer cross-linking and curing, the novel alkali-inhibiting sand and gravel material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building aggregate modification and concrete durability materials technology, specifically to a new alkali-inhibiting sand and gravel material and its preparation method. Background Technology

[0002] Alkali-silica reaction (ASR) in concrete is a core defect that severely shortens the service life of hydraulic engineering, marine engineering, saline-alkali land, and rail transit structures. The active silica components in sand and gravel aggregates, such as tuff and flint, react with alkali ions in the cement pore solution and, under continuous moisture replenishment, generate water-absorbing and expanding alkali-silica gel, causing micro-cracks inside the concrete and surface spalling, posing safety hazards in long-term use. Current engineering control methods each have shortcomings: low-alkali cement has high procurement costs; while large amounts of fly ash can reduce the alkali concentration of the system, it weakens the early strength of the concrete; silane and organic coatings can only temporarily block external moisture, and once the coating wears down and cracks, the active silica inside the aggregate will still undergo alkali expansion, failing to eradicate the defect at its source.

[0003] Current research primarily employs aggregate surface coating modification schemes, but practical applications face two major challenges: First, single silane films and inorganic powder coatings merely physically adhere to the surface of sand and gravel, making them prone to large-scale detachment under the shear impact of forced concrete mixing, resulting in rapid loss of modification function. Second, simple hydrophobic or physical adsorption of alkali ions has poor long-term effectiveness; after prolonged immersion in pore liquid, alkali ions easily desorb and rebound, leading to expansion and cracking even after many years. Lithium is a recognized highly efficient ASR inhibitor, capable of generating non-expanding lithium silicate products, but its direct incorporation into cement disrupts hydration, causing rapid setting, uneven lithium ion migration in large-volume components, and extremely low utilization efficiency. Existing technologies struggle to simultaneously achieve targeted lithium salt release and high-strength coating anchoring, lacking an integrated aggregate modification scheme that combines interfacial adhesion, active alkali suppression, and long-term hydrophobicity. Therefore, novel modified sand and gravel technologies are urgently needed to address these engineering pain points. Summary of the Invention

[0004] In order to overcome the shortcomings of the prior art, the present invention aims to provide a new alkali-suppressing sand and gravel material and its preparation method. The new alkali-suppressing sand and gravel material of the present invention has good alkali suppression effect, hydrophobic properties, wear resistance and durability.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a new material for inhibiting alkali reaction of sand and gravel, comprising a sand and gravel matrix containing active silica and a triple composite coating covering the surface of the sand and gravel matrix;

[0006] The triple composite coating consists of, from the inside out, a biomimetic mineralization interface adhesion layer, a mesoporous targeted alkali-suppressing layer, and a silane cross-linked hydrophobic outer layer.

[0007] The biomimetic mineralized interface adhesion layer is an organic-inorganic hybrid network composed of plant polyphenol components rich in catechol groups and low calcium-to-silicon ratio CSH gel.

[0008] The mesoporous targeted alkali-suppressing layer comprises MCM-41 mesoporous silica loaded with soluble lithium salt and nano-mesokaolin.

[0009] The silane cross-linked hydrophobic outer layer is a hydrophobic cross-linked network formed by the co-hydrolysis and condensation of aminosilane and alkyltriethoxysilane. The aminosilane forms a chemical bond with the surface of the mesoporous targeted alkali-inhibiting layer through a condensation reaction.

[0010] Furthermore, the plant polyphenol component is selected from one or more of tannic acid, tea polyphenols, and sodium lignosulfonate; the thickness of the biomimetic mineralized interface adhesion layer is 20-80 nm.

[0011] Furthermore, the mesoporous targeted alkali-suppressing layer also includes an aqueous polymer network, wherein the aqueous polymer is polyvinyl alcohol or sodium alginate; the thickness of the mesoporous targeted alkali-suppressing layer is 500–1500 nm.

[0012] Furthermore, the alkyltriethoxysilane is octyltriethoxysilane or isobutyltriethoxysilane; the aminosilane is 3-aminopropyltriethoxysilane.

[0013] Furthermore, the lithium salt loading of the MCM-41 mesoporous silica is 25% to 35%, and the lithium salt is lithium nitrate.

[0014] Furthermore, the preparation method of the aforementioned new alkali-suppressing sand and gravel material includes the following steps:

[0015] S1. Matrix pretreatment: The alkali-active sand and gravel matrix is ​​screened, washed with water to remove surface mud and powder impurities, dried until the surface moisture content is ≤1.0%, and cooled for later use;

[0016] S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare a weakly alkaline aqueous solution containing plant polyphenols and calcium nitrate, controlling the concentration of plant polyphenols at 1.0–3.0 g / L and the concentration of calcium ions at 0.02–0.05 mol / L, and adjust the pH of the system to 8.0–8.5; immerse the pretreated sand and gravel matrix in the solution, stir at room temperature at 20–40 r / min for 40–60 min, remove and pre-dry for later use;

[0017] S3. Mesoporous Targeted Alkali Suppression Layer Anchoring: MCM-41 mesoporous silica powder is vacuum impregnated in a 3-5 mol / L lithium nitrate solution to prepare lithium-loaded MCM-41 micropowder; the lithium-loaded MCM-41 micropowder and nano-metakaolin are dispersed in a water-ethanol mixed solvent containing 0.2-0.5 wt% water-based polymer and ultrasonically dispersed to form a stable suspension slurry; the sand and gravel treated in S2 are immersed in the slurry for coating and dried and cured at 50-65℃.

[0018] S4. Hydrophobic outer layer sealing and constant temperature curing: Mix aminosilane and alkyltriethoxysilane at a mass ratio of 1:5 to 1:10, add acid to adjust the pH and pre-hydrolyze for 15 to 30 minutes to obtain silane composite modification liquid; spray the modification liquid evenly onto the sand and gravel surface treated by S3, and cure at a constant temperature of 60 to 80°C for 12 to 24 hours. After interlayer cross-linking and curing, a new sand and gravel material with alkali-suppressing reaction is obtained.

[0019] In step S4 above, the alkoxy group in the aminosilane (KH-550) molecule is pre-hydrolyzed to generate silanol groups. These silanol groups undergo a co-condensation reaction with the silanol groups generated from the hydrolysis of alkyltriethoxysilane to form a hydrophobic crosslinked network. Simultaneously, they form Si-O-Si covalent bonds through a condensation reaction with the silanol groups abundant on the surface of the mesoporous targeted alkali-suppressing layer (derived from MCM-41 mesoporous silica and nano-metakaolin). At the same time, the amino group in the aminosilane molecule can form hydrogen bonds with the silanol groups on the surface of the mesoporous layer. The synergistic effect of these covalent bonds and hydrogen bonds constitutes the interlayer bridging structure of this invention, ensuring a strong chemical bond between the outer and middle layers.

[0020] Furthermore, the pre-drying temperature in S2 is 45-55℃, and the sand and gravel are dried until there is no free moisture on the surface.

[0021] Furthermore, the ultrasonic dispersion time in S3 is 10–20 min, and the dipping time is 15–30 min; when preparing the suspension slurry, the mass ratio of nano-kaolinite to lithium-loaded MCM-41 mesoporous silica is 1:1.5–1:2.5.

[0022] Furthermore, the pH of the pre-hydrolysis of the silane composite modified solution in S4 is controlled at 4.5–5.5, and the pre-hydrolysis temperature is room temperature.

[0023] Furthermore, the new alkali-suppressing sand and gravel material is used as concrete aggregate in marine engineering, saline-alkali land, water conservancy dams, or rail transit projects.

[0024] Compared with the prior art, the present invention has the following beneficial technical effects:

[0025] This invention presents a novel alkali-suppressing sand and gravel material employing a triple-layer composite coating design: an internally-external biomimetic mineralization interface adhesion layer, a mesoporous targeted alkali-suppressing layer, and a silane cross-linked hydrophobic outer layer. Through multiple synergistic effects, it effectively seals the internal active silica, fundamentally inhibiting the alkali-silicic acid reaction and enhancing the material's alkali-suppressing effect. An organic-inorganic hybrid network is constructed by combining plant polyphenols rich in catechol groups with low-calcium-to-silica CSH gel, and this network, along with an aqueous polymer network and aminosilane, forms an interlayer bridging structure. This solves the engineering pain points of traditional mesoporous powders or physical coatings, which suffer from significant peeling and severe functional degradation under the intense mixing conditions of concrete. The outer layer of the material utilizes a hydrophobic cross-linked network formed by the co-hydrolysis and condensation of aminosilane and alkyltriethoxysilane, achieving a water contact angle of 128° to 142° for the modified sand and gravel. This successfully constructs a highly hydrophobic alkali-suppressing defense line, effectively blocking external moisture intrusion, reducing the moisture transport channels necessary for alkali-aggregate reaction, and further enhancing the long-term alkali-suppressing effect. The MCM-41 mesoporous silica loaded with soluble lithium salts in the mesoporous targeted alkali suppression layer can release lithium ions at the active silica interface on the aggregate surface to achieve local alkali suppression. Meanwhile, the nano-mesokaolin can induce micro-regional geopolymerization reaction, effectively preventing the problem of alkali ion backflow failure that is easy to cause by traditional physical adsorption, and eliminating safety hazards in long-term service. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment prepares a novel sand and gravel material that inhibits alkali reaction, and the specific steps are as follows:

[0029] S1. Matrix pretreatment: Take 1000g of tuff manufactured sand with high alkali activity, sieve out particles with a particle size of 0.15~4.75mm, use them as the aggregate for the test in this embodiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is about 0.5%, and cool them for later use.

[0030] S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare 2L of weakly alkaline aqueous solution. Weigh 4.0g of tannic acid and 14.17g of calcium nitrate, and dissolve them in deionized water. Adjust the pH of the system to 8.2 using a dilute sodium hydroxide solution. Prepare the weakly alkaline aqueous solution immediately. After complete dissolution, immerse all 1000g of the pretreated sand and gravel substrate from S1 into the solution and react slowly at 30r / min for 50min at room temperature. After removal, pre-dry in a 50℃ oven until no free moisture remains on the sand and gravel surface. SEM analysis showed that a hybrid adhesion layer with a thickness of approximately 50nm was formed on the surface.

[0031] S3. Mesoporous targeted alkali suppression layer anchoring: Weigh 20g of MCM-41 mesoporous silica powder, place it in 1L of 4mol / L lithium nitrate aqueous solution for vacuum impregnation, then filter and separate, and dry to obtain lithium-loaded MCM-41 micro powder with a lithium salt loading of 30%.

[0032] Weigh 10g of nano-kaolin and 20g of lithium-loaded MCM-41 micro powder (mass ratio 1:2), disperse them in 300mL of water-ethanol mixed solvent containing 0.9g of polyvinyl alcohol (PVA) (water to ethanol volume ratio 1:1), and ultrasonically disperse for 15min to form a stable suspension slurry.

[0033] 1000g of sand treated with S2 was immersed in the slurry for 20 minutes, then removed and dried at 60℃. The SEM cross-sectional measurement showed that the thickness of this layer was approximately 1000nm.

[0034] S4. Hydrophobic Outer Layer Sealing and Constant Temperature Curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 40g of octyltriethoxysilane (mass ratio 1:8), mix, add 25mL of deionized water and glacial acetic acid, adjust the pH to 5.0, and pre-hydrolyze at room temperature for 20min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the surface of the sand and gravel treated in S3, and then place it in a constant temperature oven at 70℃ for 18h for curing. After interlayer crosslinking and curing, the finished alkali-suppressing sand and gravel new material is obtained.

[0035] Example 2

[0036] This embodiment prepares a novel sand and gravel material that inhibits alkali reaction, and the specific steps are as follows:

[0037] S1. Matrix pretreatment: Take 1000g of high-alkali active river sand containing active silica, sieve out particles with a particle size of 0.15~4.75mm, use them as the aggregate for the test in this embodiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is ≤1.0%, and cool them for later use.

[0038] S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare 2L of weakly alkaline aqueous solution. Weigh 2.0g of tea polyphenols and 9.45g of calcium nitrate, and dissolve them in deionized water. Adjust the pH of the system to 8.0 using a dilute sodium hydroxide solution. Prepare the weakly alkaline aqueous solution immediately. After complete dissolution, immerse all 1000g of the pretreated sand and gravel substrate from S1 into the solution and react slowly at 20r / min for 60min at room temperature. After removal, pre-dry in a 45℃ oven until no free moisture remains on the sand and gravel surface. SEM analysis showed that a hybrid adhesion layer with a thickness of approximately 20nm was formed on the surface.

[0039] S3. Mesoporous targeted alkali suppression layer anchoring: Weigh 20g of MCM-41 mesoporous silica powder, place it in 1L of 3mol / L lithium nitrate aqueous solution for vacuum impregnation, then filter and separate, and dry to obtain lithium-loaded MCM-41 micro powder with a lithium salt loading of 25%.

[0040] Weigh 10g of nano-kaolin and 15g of lithium-loaded MCM-41 micro powder (mass ratio 1:1.5), disperse them in 250mL of a water-ethanol mixed solvent containing 0.5g of sodium alginate (water to ethanol volume ratio 7:3), and ultrasonically disperse for 10min to form a stable suspension slurry.

[0041] 1000g of sand treated with S2 was immersed in the slurry for 30 minutes, then removed and dried at 50℃. The SEM cross-sectional measurement showed that the thickness of this layer was approximately 500nm.

[0042] S4. Hydrophobic Outer Layer Sealing and Constant Temperature Curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 25g of isobutyltriethoxysilane (mass ratio 1:5), mix them, add 25mL of deionized water and glacial acetic acid, adjust the pH to 4.5, and pre-hydrolyze at room temperature for 30min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the surface of the sand and gravel treated in S3, and then place it in a constant temperature oven at 60℃ for 24h for curing. After interlayer crosslinking and curing, the finished alkali-suppressing sand and gravel new material is obtained.

[0043] Example 3

[0044] This embodiment prepares a novel sand and gravel material that inhibits alkali reaction, and the specific steps are as follows:

[0045] S1. Matrix pretreatment: Take 1000g of high-alkali active flint crushed stone, sieve out particles with a particle size of 0.15~4.75mm, use them as the aggregate for the test in this embodiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is ≤1.0%, and cool them for later use.

[0046] S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare 2L of weakly alkaline aqueous solution. Weigh 6.0g of sodium lignosulfonate and 23.62g of calcium nitrate, and dissolve them in deionized water. Adjust the pH of the system to 8.5 using a dilute sodium hydroxide solution. Prepare the weakly alkaline aqueous solution immediately. After complete dissolution, immerse all 1000g of the pretreated sand and gravel substrate from S1 into the solution and react slowly at 40r / min for 40min at room temperature. After removal, pre-dry in a 55℃ oven until no free moisture remains on the sand and gravel surface. SEM analysis showed that a hybrid adhesion layer with a thickness of approximately 80nm was formed on the surface.

[0047] S3. Mesoporous targeted alkali suppression layer anchoring: Weigh 20g of MCM-41 mesoporous silica powder, place it in 1L of 5mol / L lithium nitrate aqueous solution for vacuum impregnation, then filter and separate, and dry to obtain lithium-loaded MCM-41 micro powder with a lithium salt loading of 35%.

[0048] Weigh 10g of nano-kaolin and 25g of lithium-loaded MCM-41 micro powder (mass ratio 1:2.5), disperse them in 350mL of water-ethanol mixed solvent containing 1.75g ​​of polyvinyl alcohol (PVA) (water to ethanol volume ratio 7:3), and ultrasonically disperse for 20min to form a stable suspension slurry.

[0049] 1000g of sand treated with S2 was immersed in the slurry for 15 minutes, then removed and dried at 65℃. The SEM cross-sectional measurement showed that the thickness of this layer was approximately 1500nm.

[0050] S4. Hydrophobic Outer Layer Sealing and Constant Temperature Curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 50g of octyltriethoxysilane (mass ratio 1:10), mix, add 25mL of deionized water and glacial acetic acid, adjust the pH to 5.5, and pre-hydrolyze at room temperature for 15min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the surface of the sand and gravel treated in S3, and then place it in an 80℃ constant temperature oven for curing for 12h. After interlayer crosslinking and curing, the finished alkali-suppressing sand and gravel new material is obtained.

[0051] Comparative Example 1

[0052] The main difference between this comparative example and Example 1 is that the biomimetic mineralization interface adhesion layer preparation process (S2) and the mesoporous targeted alkali-suppressing layer anchoring process (S3) are omitted. Only a single silane hydrophobic coating is used to modify the sand and gravel matrix. The remaining raw materials, equipment, and process parameters are consistent with those in Example 1. The specific steps are as follows:

[0053] S1. Matrix pretreatment: Take 1000g of tuff manufactured sand with high alkali activity, sieve out particles with a particle size of 0.15~4.75mm, use them as aggregate for this comparative experiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is about 0.5%, and cool them for later use.

[0054] S2. Hydrophobic outer layer sealing and isothermal curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 40g of octyltriethoxysilane (mass ratio 1:8), mix, add 25mL of deionized water and glacial acetic acid, adjust the pH to 5.0, and pre-hydrolyze at room temperature for 20min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the pretreated sand and gravel surface, and then place it in a 70℃ isothermal oven for curing for 18h to obtain a control sample with only a single-layer silane protective structure.

[0055] Comparative Example 2

[0056] The main difference between this comparative example and Example 1 is that the preparation process of the S2 biomimetic mineralized interface adhesion layer is omitted, and the polyvinyl alcohol water-based polymer crosslinking network is not added during the S3 slurry preparation process; only simple inorganic powder mixing and coating is used. All other raw materials, equipment, and process parameters remain the same as in Example 1. The specific steps are as follows:

[0057] S1. Matrix pretreatment: Take 1000g of tuff manufactured sand with high alkali activity, sieve out particles with a particle size of 0.15~4.75mm, use them as aggregate for this comparative experiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is about 0.5%, and cool them for later use.

[0058] S2. Mesoporous Targeted Alkali-Inhibiting Layer Anchoring: Weigh 20g of MCM-41 mesoporous silica powder and place it in 1L of 4mol / L lithium nitrate aqueous solution for vacuum impregnation. After filtration and separation, dry to obtain lithium-loaded MCM-41 micropowder with a lithium salt loading of 30%. Weigh 10g of nano-kaolin and 20g of lithium-loaded MCM-41 micropowder (mass ratio 1:2) and directly disperse them in 300mL of water-ethanol mixed solvent (water to ethanol volume ratio 1:1). Do not add polyvinyl alcohol to the system. Ultrasonically disperse for 15min to form a suspension slurry. Immerse 1000g of pretreated sand and gravel in the slurry for 20min, remove and dry at 60℃ for curing.

[0059] S3. Hydrophobic outer layer sealing and isothermal curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 40g of octyltriethoxysilane (mass ratio 1:8), mix them, add 25mL of deionized water and glacial acetic acid, adjust the pH to 5.0, and pre-hydrolyze at room temperature for 20min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the surface of the sand and gravel treated above, and then place it in a 70℃ isothermal oven for curing for 18h to obtain a control sample.

[0060] Comparative Example 3

[0061] The main difference between this comparative example and Example 1 is that no nano-kaolin is added during the preparation of the S3 slurry; only a single lithium-loaded MCM-41 mesoporous powder is used for alkali suppression modification. All other raw materials, equipment, and process parameters remain the same as in Example 1. The specific steps are as follows:

[0062] S1. Matrix pretreatment: Take 1000g of tuff manufactured sand with high alkali activity, sieve out particles with a particle size of 0.15~4.75mm, use them as aggregate for this comparative experiment, wash off the mud and powder impurities on the surface with clean water, put them in an oven at 105℃ and dry them until the surface moisture content is about 0.5%, and cool them for later use.

[0063] S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare 2L of weakly alkaline aqueous solution, weigh 4.0g of tannic acid and 9.73g of calcium nitrate, and dissolve them in deionized water; adjust the pH of the system to 8.2 using a dilute sodium hydroxide solution. Immerse all 1000g of sand and gravel substrate pretreated in S1 into this solution, and stir slowly at 30r / min for 50min at room temperature. After removal, place it in a 50℃ oven to pre-dry until there is no free moisture on the surface of the sand and gravel.

[0064] S3. Mesoporous Targeted Alkali-Inhibiting Layer Anchoring: Weigh 20g of MCM-41 mesoporous silica powder and place it in 1L of 4mol / L lithium nitrate aqueous solution for vacuum impregnation. After filtration and separation, dry to obtain lithium-loaded MCM-41 micropowder with a lithium salt loading of 30%. Weigh only 20g of lithium-loaded MCM-41 micropowder and disperse it in 300mL of a water-ethanol mixed solvent containing 0.9g of polyvinyl alcohol (PVA) (water to ethanol volume ratio 1:1). Ultrasonically disperse for 15min to form a stable suspension slurry. Immerse 1000g of sand and gravel treated in S2 into this slurry for 20min, remove and dry at 60℃ for curing.

[0065] S4. Hydrophobic Outer Layer Sealing and Constant Temperature Curing: Weigh 5g of 3-aminopropyltriethoxysilane (KH-550) and 40g of octyltriethoxysilane (mass ratio 1:8), mix, add 25mL of deionized water and glacial acetic acid, adjust the pH to 5.0, and pre-hydrolyze at room temperature for 20min to obtain a silane composite modified solution. Use an atomizing nozzle to evenly spray all the modified solution onto the surface of sand and gravel treated in S3, and then place it in a constant temperature oven at 70℃ for 18h for curing. After interlayer crosslinking and curing, a control sample is obtained.

[0066] Performance testing

[0067] The novel alkali-suppressing sand and gravel materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, with untreated raw sand and gravel serving as a blank control. In Comparative Example 3, no nano-kaolin was added to the suspension slurry, and the amount of lithium-loaded MCM-41 micro powder used was the same as in Example 1. The test methods are as follows:

[0068] (1) Expansion rate test of alkali-silicic acid reaction

[0069] Tests were conducted according to ASTM C1260 standard, simultaneously conforming to Appendix B of GB / T 14684-2022 "Construction Sand" - Rapid Test Method for Alkali Activity. Using untreated raw sand and gravel, finished products from Examples 1-3, and Comparative Examples 1-3 as aggregates, 25mm × 25mm × 285mm mortar specimens were prepared according to standard mix proportions. Three specimens were formed for each mix proportion. The initial length was measured immediately after demolding. The specimens were then placed in a curing container, and a 1mol / L sodium hydroxide solution was added, ensuring the liquid level was approximately 30mm above the specimen surface. The container was sealed and placed in an 80℃ constant temperature water bath. Specimens were removed at 3, 7, 10, and 14 days after immersion. After drying the surface, the length was measured, and the average value of the three specimens was used to calculate the expansion rate at each age. A lower expansion rate at 14 days indicates a more significant alkali suppression effect.

[0070] (2) Silicon leaching inhibition rate test

[0071] Weigh 50g each of untreated raw sand and gravel, the finished products of Examples 1-3 and Comparative Examples 1-3, and place them in 250mL polyethylene bottles. Add 100mL of saturated calcium hydroxide solution (pH≈12.5), seal the bottles, and let them stand at 25℃ for 28 days, ensuring they are sealed and protected from light throughout the process. Gently shake the bottles every 7 days to ensure sufficient solid-liquid contact and prevent carbonization and failure of the solution. After the period, take the supernatant, filter it through a 0.45μm filter membrane, and determine the silicon ion concentration in the solution using inductively coupled plasma optical emission spectrometry (ICP-OES). Calculate the silicon leaching inhibition rate of each specimen (based on untreated raw sand and gravel) using the following formula: Silicon leaching inhibition rate (%) = (C0−C1) / C0×100%, where: C0 is the silicon ion concentration in the soaking solution of untreated raw sand and gravel, and C1 is the silicon ion concentration in the soaking solution of each specimen. The higher the silicon leaching inhibition rate, the more significant the inhibitory effect of the coating on the leaching of active silica.

[0072] (3) Surface hydrophobicity test

[0073] Ten finished sand and gravel particles from Examples 1-3 and Comparative Examples 1-3 with similar particle sizes (2.36-4.75 mm) and relatively smooth surfaces were selected from each sample and laid in a single layer on a glass slide. Using a contact angle meter, under ambient conditions of 25°C and 50%-60% relative humidity, 2 μL of deionized water was dropped onto the sand and gravel surface. After standing for 10 seconds, the static water contact angle was measured. Ten particles were measured in each group, and three different locations were measured for each particle. The arithmetic mean was taken as the final contact angle value. A contact angle > 120° indicates a well-constructed hydrophobic outer layer.

[0074] (4) Water immersion adhesion test of coating

[0075] Take 100g each of the finished sand and gravel from Examples 1-3 and Comparative Examples 1-3, place them in beakers, add sufficient deionized water to completely submerge the sand and gravel, cover, and place in a 60℃ constant temperature water bath for continuous soaking for 7 days. Change the deionized water every 24 hours during the soaking period. After 7 days, remove the sand and gravel, absorb the free moisture on the surface with filter paper, and allow them to air dry naturally for 24 hours. Observe the peeling, flaking, or cracking of the coating on the surface of each sand and gravel specimen by visual inspection and scanning electron microscopy (SEM). A complete coating without visible defects is considered qualified.

[0076] (5) Test of resistance to mechanical wear during mixing

[0077] Weigh 500g each of the finished sand and gravel from Examples 1-3 and Comparative Examples 1-3, and mix them with an equal mass (500g) of P·O42.5 grade Portland cement paste (water-cement ratio 0.45, cement paste mass approximately 500g, mass ratio of sand and gravel 1:1). Place the mixture in a single-shaft forced concrete mixer and stir at 45r / min for 5min to simulate the aggregate-cement mixture process in actual engineering. After mixing, remove the sand and gravel particles, rinse them repeatedly with clean water to remove residual cement paste from the surface, then ultrasonically clean them with deionized water for 3min, and dry them in a 105℃ oven. Subsequently: ① Re-measure the 14d ASR expansion rate of the sand and gravel after wear according to the method in (1) above; ② Observe the microstructure of the coating on the surface of the sand and gravel after wear using SEM, and count the percentage of residual coating area. The smaller the change in expansion rate after wear and the higher the percentage of residual coating area, the stronger the interfacial adhesion of the coating and the better the resistance to mechanical peeling.

[0078] The test results are shown in Table 1.

[0079] Note: "—" indicates that the test was not performed or there is no evaluation object; "intact" in the coating condition after water immersion means no peeling, flaking or cracking, and "flaking" means that there is obvious coating detachment; the percentage of residual coating area after wear is obtained by statistical analysis of SEM images, reflecting the degree of coating retention after mechanical stirring.

[0080] Table 1: Performance Tests

[0081]

[0082] As shown in Table 1 (the data in each group are the arithmetic mean of three parallel specimen tests, and the relative deviations of the main indicators of each example are controlled within ±5%, indicating good reproducibility), the 14-day ASR expansion rate of the untreated raw sand and gravel was 0.385%, far exceeding the 0.10% safety limit specified in ASTM C1260, classifying it as a high-alkali reactive aggregate. The 14-day ASR expansion rates of Examples 1-3 were 0.024%, 0.031%, and 0.018%, respectively, which were 93.8%, 91.9%, and 95.3% lower than those of the untreated raw sand and gravel, and all were far below the 0.10% safety threshold; the 28-day silica leaching inhibition rates were 96.5%, 91.2%, and 98.1%, respectively, and the water contact angles were 135°, 128°, and 142°, respectively, all greater than 120°, indicating that the triple-layer composite coating has both excellent alkali inhibition ability and good hydrophobic protection effect. The stringent conditions of 80°C, 1 mol / L NaOH solution, and 14 days of continuous immersion in the ASTM C1260 standard method are sufficient to allow the alkali solution to gradually penetrate to the aggregate surface through the coating edges, capillary channels, and microscopic defects. The low expansion rate measured after 14 days of immersion is the result of the synergistic effect of hydrophobic physical barrier and lithium salt chemical alkali inhibition; physical barrier alone cannot achieve such significant expansion inhibition—the expansion rate of Comparative Example 1 (only silane hydrophobic layer, without lithium-loaded alkali inhibition layer) under the same test conditions is evidence of this. Meanwhile, the 28-day silicon leaching inhibition rate data of Examples 1-3 directly prove the chemical alkali inhibition effect achieved by lithium salt slow release. After 7 days of water immersion at 60°C, the coatings of Examples 1-3 and Comparative Example 3 remained intact, while Comparative Example 1 and Comparative Example 2 showed localized hydrolytic cracking, indicating that the biomimetic mineralized adhesion layer and the water-based polymer crosslinking network are crucial to the hydrothermal interface stability of the coating. After mechanical agitation and wear, the expansion rates of Examples 1-3 only increased slightly to 0.028%, 0.036%, and 0.023%, respectively, with residual coating area ratios of 95.2%, 91.5%, and 97.4%, respectively. In contrast, the expansion rate of Comparative Example 1 after wear increased sharply from 0.165% to 0.280%, with a residual coating area of ​​only 18.6%. The expansion rate of Comparative Example 2 after wear surged from 0.086% to 0.265%, with a residual coating area of ​​only 12.7%. This further demonstrates that without a biomimetic adhesion substrate and a polymer crosslinking network, the coating peels off significantly under strong agitation conditions, severely degrading its alkali-suppressing function. It should be noted that this test used a stirring condition of 45 r / min for 5 min, aiming to provide a standardized comparative evaluation method, focusing on the relative retention of the coating after mechanical shearing. The approximately 5-fold difference in residual area between Comparative Example 1 (18.6%) and Example 1 (95.2%) is sufficient to demonstrate the significant superiority of the triple composite coating of the present invention in terms of resistance to mechanical peeling. This comparative conclusion is consistent under different stirring intensities.

[0083] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0085] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.

Claims

1. A novel alkali-inhibiting sand and gravel material, characterized in that, It includes a sand and gravel matrix containing active silica and a triple composite coating covering the surface of the sand and gravel matrix; The triple composite coating consists of, from the inside out, a biomimetic mineralization interface adhesion layer, a mesoporous targeted alkali-suppressing layer, and a silane cross-linked hydrophobic outer layer. The biomimetic mineralized interface adhesion layer is an organic-inorganic hybrid network composed of plant polyphenol components rich in catechol groups and low calcium-to-silicon ratio CSH gel. The mesoporous targeted alkali-suppressing layer comprises MCM-41 mesoporous silica loaded with soluble lithium salt and nano-mesokaolin. The silane cross-linked hydrophobic outer layer is a hydrophobic cross-linked network formed by the co-hydrolysis and condensation of aminosilane and alkyltriethoxysilane. The aminosilane forms a chemical bond with the surface of the mesoporous targeted alkali-inhibiting layer through a condensation reaction.

2. The novel alkali-inhibiting sand and gravel material according to claim 1, characterized in that, The plant polyphenol component is selected from one or more of tannic acid, tea polyphenols, and sodium lignosulfonate; the thickness of the biomimetic mineralized interface adhesion layer is 20-80 nm.

3. The novel alkali-inhibiting sand and gravel material according to claim 1, characterized in that, The mesoporous targeted alkali-inhibiting layer also contains an aqueous polymer network, wherein the aqueous polymer is polyvinyl alcohol or sodium alginate; the thickness of the mesoporous targeted alkali-inhibiting layer is 500–1500 nm.

4. The novel alkali-inhibiting sand and gravel material according to claim 1, characterized in that, The alkyltriethoxysilane is octyltriethoxysilane or isobutyltriethoxysilane; the aminosilane is 3-aminopropyltriethoxysilane.

5. The novel alkali-inhibiting sand and gravel material according to claim 1, characterized in that, The lithium salt loading of the MCM-41 mesoporous silica is 25% to 35%, and the lithium salt is lithium nitrate.

6. A method for preparing a novel alkali-inhibiting sand and gravel material as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Matrix pretreatment: The alkali-active sand and gravel matrix is ​​screened, washed with water to remove surface mud and powder impurities, dried until the surface moisture content is ≤1.0%, and cooled for later use; S2. In-situ mineralization and preparation of biomimetic adhesion layer: Prepare a weakly alkaline aqueous solution containing plant polyphenols and calcium nitrate, controlling the concentration of plant polyphenols at 1.0–3.0 g / L and the concentration of calcium ions at 0.02–0.05 mol / L, and adjust the pH of the system to 8.0–8.5; immerse the pretreated sand and gravel matrix in the solution, stir at room temperature at 20–40 r / min for 40–60 min, remove and pre-dry for later use; S3. Mesoporous Targeted Alkali Suppression Layer Anchoring: MCM-41 mesoporous silica powder is vacuum impregnated in a 3-5 mol / L lithium nitrate solution to prepare lithium-loaded MCM-41 micropowder; the lithium-loaded MCM-41 micropowder and nano-metakaolin are dispersed in a water-ethanol mixed solvent containing 0.2-0.5 wt% water-based polymer and ultrasonically dispersed to form a stable suspension slurry; the sand and gravel treated in S2 are immersed in the slurry for coating and dried and cured at 50-65℃. S4. Hydrophobic outer layer sealing and constant temperature curing: Mix aminosilane and alkyltriethoxysilane at a mass ratio of 1:5 to 1:10, add acid to adjust the pH and pre-hydrolyze for 15 to 30 minutes to obtain silane composite modification liquid; spray the modification liquid evenly onto the sand and gravel surface treated by S3, and cure at a constant temperature of 60 to 80°C for 12 to 24 hours. After interlayer cross-linking and curing, a new sand and gravel material with alkali-suppressing reaction is obtained.

7. The method for preparing the new alkali-suppressing sand and gravel material according to claim 6, characterized in that, The pre-drying temperature in S2 is 45-55℃, and the sand and gravel are dried until there is no free moisture on the surface.

8. The method for preparing the new alkali-suppressing sand and gravel material according to claim 6, characterized in that, The ultrasonic dispersion time in S3 is 10-20 min, and the dipping time is 15-30 min. When preparing the suspension slurry, the mass ratio of nano-kaolinite to lithium-loaded MCM-41 mesoporous silica is 1:1.5 to 1:2.

5.

9. The method for preparing the new alkali-suppressing sand and gravel material according to claim 6, characterized in that, The pH of the pre-hydrolysis of the silane composite modified solution in S4 is controlled at 4.5–5.5, and the pre-hydrolysis temperature is room temperature.

10. The application of a novel alkali-inhibiting sand and gravel material according to any one of claims 1-5, characterized in that, Used as concrete aggregate in marine engineering, saline-alkali land, water conservancy dams or rail transit projects.